Investigation of non-tuberculous mycobacteria in a primary hospital from southeastern China - Xinling Pan; Yangxiao Zhou; Zhaoxia Li; Jun Zhang; Li Hong; Yunzhen Shi; Guo-Gang Li (Journal of Infection in Developing Countries)
Introduction: Non-tuberculous mycobacterium (NTM) can colonize the human body, leading to opportunistic infection. This study was conducted to analyze the NTM species composition in a primary hospital and investigate the potential features of the patients with different NTM species.